Influence of A1, 3 Strain on the Stereochemical Outcome of Acid‐Mediated Amido Cyclization in the Synthesis of 2‐(4‐Methoxyphenyl)‐3, 4‐(dihydroxy)piperidines. Issue 9 (19th February 2016) - Ramakrishna, Katakam; Jagadeesh, Yerri; Ramakrishna, K. V. S; Rao, Joshi Laxmikanth; Rao, Batchu Venkateswara
Abstract: The synthesis of 2‐(4‐methoxyphenyl)‐3, 4‐(dihydroxy)piperidines was accomplished by using ethyl p ‐methoxycinnamate as the starting material and an acid‐mediated amido cyclization reaction as the key step. This short and straightforward strategy avoids extra steps to create the chiral center and does not require a leaving group at the benzylic carbon. This study also showed that the stereochemical outcome of the cyclization reaction is influenced more by allylic 1, 3‐strain (A 1, 3 strain) than by the participation of a neighboring group. Abstract : A short and straightforward strategy for the stereoselective synthesis of 2‐(4‐methoxyphenyl)‐3, 4‐(dihydroxy)piperidines was developed. The key step of this synthetic approach involved an acid‐mediated amido cyclization reaction, in which allylic 1, 3‐strain (A 1, 3 strain) was the controlling element in determining the stereochemical outcome of the reaction.